Determination of vitamin K from fermented foods - Fabritius, Mikael (fi=Turun yliopisto|en=University of Turku|, 2018)
A quick and sensitive analysis method was developed for the analysis of vitamin K compounds, including phylloquinone (PK) and menaquinones (MK-n). The method utilizes ultra-high performance liquid chromatography tandem mass spectrometry with atmospheric pressure chemical ionization (UHPLC-APCI-MS/MS). Non-chlorinated mobile phase composition was optimized for separation of eight vitamin K compounds on a reversed phase column in 10 minutes. Sample treatment with liquid and solid phase extractions and by the use of MK-4 as an internal standard enabled the quantitation of microgram level of vitamin K compounds in food. The UHPLC-MS/MS analysis is one of the fastest described methods for vitamin K analysis and consumes low amounts of solvents per sample. Sensitivity of the developed method is comparable to the other previously described vitamin K analysis methods using similar equipment. The method was tested with various different food samples and it was determined to be sufficient for most food matrices. Only one limiting factor was detected: high fat content of food. Food samples with less than 8% fat were quantified properly with high signal intensity. With higher fat content the sensitivity for each vitamin K compound would have to be checked before quantification. Due to restrictions in schedule the method was not optimized further for high-fat food samples. The method was used to screen and quantify vitamin K from 17 fermented food products. The highest amount of PK was detected in kimchi (42.4 ± 2.5 µg/100 g fresh weight), whereas the highest MK-7 content was detected in natto (901.7 ± 29.2). MK-9 was detected only in kefir (4.5 ± 2.4). Two Chinese fermented soybean pastes contained significant amount of MK-6 (4.5 ± 0.1 and 35.8 ± 15.6), MK-7 (86.3 ± 0.2, 11.9 ± 2.9), and MK-8 (44.0 ± 1.4 and, 22.3 ± 3.3).